Further evaluation of contingencies on lying about homework completion. (8th April 2021) - Stocco, Corey S.; Moline, Adam D.; Bowar, Stephanie
Abstract: Lying during childhood can have a negative impact on the quality of relationships between caregivers and children. Although caregivers have identified lying as a major concern, few studies have evaluated the conditions under which lying about socially significant events is more or less probable. This study extended Sauter et al. (2020) in two ways. First, we assessed the extent to which modified baseline procedures reliably evoked lies about homework completion or academic dishonesty. Second, we evaluated the effects of an intervention package comprised of praise‐based components recommended by professionals and supported by previous research. When the praise‐based intervention was ineffective, we implemented a tangible intervention comprised of rules, and differential reinforcement. All participants lied about academic dishonesty under baseline conditions and continued to do so when researchers implemented the praise‐based intervention. In contrast, the tangible intervention increased honest reports for all participants and decreased academic dishonesty for two of three participants. These effects were replicated in probe sessions conducted by one participant's mother.